Single-cell atlas of human skin implicates APOE pro-inflammatory signaling in diabetic foot ulcers - Yin, Yating; Li, Li; Liu, Mingen; Wang, Bin (Frontiers in Immunology, 2025)
BackgroundDiabetic foot ulcers (DFU) are a major global complication of diabetes mellitus, yet their underlying mechanisms remain incompletely understood. Fibroblasts are key regulators in the finely tuned process of wound healing.MethodsSingle-cell RNA sequencing was performed on human skin tissues to delineate cellular composition and transcriptional profiles.ResultsWe identified a distinct fibroblast population overexpressing Apolipoprotein E (APOE) in DFU patients with non-healing wounds. APOE+ fibroblasts were predominantly enriched in DFU patients, and exhibited strong associations with fat cell differentiation and the regulation of epithelial cell proliferation. Metabolic pathway analysis indicated that APOE+ fibroblasts might play a role in the onset and progression of diabetes through the Drug Metabolism-Cytochrome P450 pathway. Pseudotime analysis suggested that APOE+ fibroblasts are in an intermediate differentiation state. CellChat analysis highlighted the significant role of the FGF signaling pathway in DFU. Immunohistochemical staining confirmed upregulated APOE expression in DFU tissues. Ex vivo experiments demonstrated that soluble APOE accelerated fibrosis and inflammation in human fibroblasts, suggesting its detrimental role. Furthermore, high glucose elevated APOE expression and induced a profibrotic and inflammatory phenotype in human fibroblasts.ConclusionsThis study provides critical insights into the differences between healthy and DFU fibroblasts, identifying specific cell populations that may influence DFU healing. These findings may contribute to future therapeutic development for DFU.